Shear-Induced Crystallization of Poly(lactic acid)/Graphene Nanocomposite - Mojdeh Reghat (علوم و تکنولوژی پلیمر, 2016)
The method by which a polymer structure develops during polymer processing has important effects on the quality of final product. Among the structural development methods, crystallization process is of the highest interest. In this study, isothermal crystallization behavior of poly(lactic acid) (PLA) and its nanocomposites with graphene was investigated under quiescent and shear conditions. Neat PLA and its noncomposites containing 0.5, 1, 2 and 3 wt% graphene were prepared via melt mixing method in an internal mixer. Structural analysis and crystallization behavior of the nanocomposites before and after applying shear stress were investigated by differential scanning calorimetric (DSC) analyses. The effect of shear rate, shear time and concentration of nano-graphene on the progress of crystallization process was studied at 135°C using rheometic method. The preshear rates of 0.1, 0.3, 0.5, 1.1 and 1.8 s-1 were applied at temperature of 200°C for 60 s. The increase of storage modulus indicated to the formation of crystalline structure. Results showed that by increasing nano-graphene content the storage modulus was rapidly reached its ultimate value and the induction time of crystallization was decreased. The crystallization process was enhanced by applying preshear stress, particularly in high concentration of nano-graphene platelets. Increasing the shear time to 300 and 600 s, the induction time was decreased. DSC analysis results showed that degree of crystallization increased after applying preshear stress.